HIV-associated cognitive disorders in perinatally infected children and adolescents: a novel composite cognitive domains score. (14th December 2018) - Phillips, Nicole J.; Hoare, Jacqueline; Stein, Dan J.; Myer, Landon; Zar, Heather J.; Thomas, Kevin G. F.
ABSTRACT: Accurate assessment of HIV-associated cognitive disorders in perinatally infected children and adolescents is challenging. Assessments of general intellectual functioning, or global cognition, may not provide information regarding domain-specific strengths and weaknesses, and may therefore fail to detect, impaired trajectories of development within particular cognitive domains. We compare the efficacy of global cognitive scores to that of composite cognitive domain scores in detecting cognitive disorders in a sample of perinatally HIV-infected children, and a demographically matched HIV negative control group, drawn from the Cape Town Adolescent Antiretroviral Cohort (CTAAC) study. All children were administered a comprehensive neuropsychological test battery. Using data from that test battery, we created ten separate composite cognitive domains: general intellectual functioning, attention, working memory, visual memory, verbal memory, language, visual spatial ability, motor coordination, processing speed and executive function. Within each domain, each test bore a high level of association with each of the other tests in that domain (Cronbach's α  ≥ .70 for all domains). We found that composite domain scores calculated on whole-sample data were significantly higher than those calculated using control-sample data. Our comparison of a global cognitive score to composite domain scores suggested that the latter provided more detailed information (regarding strengths, weaknesses, areas of impairment), and when compared to global scores, were more sensitive in detecting HIV-associated cognitive disorders, and were able to distinguish HIV-infected patients from uninfected controls. Hence, we recommend using this method of composite cognitive domains scores, rather than global aggregate scores, when assessing cognitive function in paediatric HIV. This method provides a convenient and relatively accurate assessment that might help with cross-cultural and cross-region comparisons as researchers try to detect cognitive impairment patterns in HIV-infected children and adolescents globally.